The Relevance of a Diagnostic and Counseling Service for People Living With HTLV-1/2 in a Metropolis of the Brazilian Amazon - Lopes, Felipe Teixeira; de Sousa, Renata Santos; Carvalho Gomes, Jayanne L.; Vallinoto, Mariana Cayres; de Lima, Aline Cecy Rocha; Lima, Sandra Souza; Freitas, Felipe Bonfim; Feitosa, Rosimar N. Martins; Rangel da Silva, Andrea Nazaré M.; Machado, Luiz Fernando A.; Aben-Athar, Cintia Y. P.; Maia da Silva, Eduardo Leitão; et al. (Frontiers in Public Health, 2022)
Introduction: To identify the prevalence of infection in the urban area of the capital city of Belém, Brazil, the Laboratory of Virology of the Federal University of Pará implemented, as a public service, serological screening for human T-lymphotropic viruses 1 and 2 (HTLV-1/2) infection and, if necessary, counseling service and referral to specialized medical care. The project is funded by the National Council of Science and Technology, the Ministry of Health of Brazil and the Pan American Health Organization. Methods: From January 2020 to June 2021, 1,572 individuals of both sexes were approached to answer a questionnaire and were tested using an enzyme immunoassay (Murex HTLV-I+II, DiaSorin, Dartford, UK). Seropositive samples were confirmed as HTLV-1 and HTLV-2 infection by line immunoassay (INNO-LIA® HTLV I/II Score, Fujirebio, Japan) and/or by real-time polymerase chain reaction. G and Fisher's exact tests were applied to identify the association between epidemiological characteristics and HTLV-1/2 infection. Results: Of the 1,572 screened individuals, 63.74% were females between the ages of 30 and 59 years (49.04%). Infection was confirmed in six individuals (0.38%), among whom three (0.19%) were infected with HTLV-1 and three with HTLV-2 (0.19%). Blood transfusion before 1993 was the main risk factor associated with the route of exposure to the virus (p = 0.0442). The infected individuals were referred to a counseling session with a nursing professional, and two patients who manifested signs and symptoms suggestive of myelopathy associated with HTLV were referred to a neurologist. Conclusion: The implementation of the screening service revealed the occurrence of moderate endemicity of HTLV-1/2 in Belém, reinforcing the importance of continuing the service as a means of establishing an early diagnosis and providing counseling as a measure to prevent and control viral transmission in the general population.